'Everywhere Surveillance': Global Surveillance Regimes as Techno-Securitization. (2nd January 2020) - Petit, Patrick
ABSTRACT: The Snowden leaks revealed how surveillance agencies conduct surveillance along all geographical scales, from the global to the local. A close look at National Security Agency (NSA) surveillance infrastructures demonstrates how these infrastructures have expanded globally. This expansion is based on technological advances, collaborations between domestic and foreign agencies and ambiguous liaisons between public and private actors. The emergence of global surveillance has to be seen in the context of the increasing techno-securitization of societies that has made surveillance technologies a key technique of government. State-led efforts to secure societies against global threats such as terrorism have turned everyone into a potential threat and therefore into a target of surveillance technologies. Hence, analyses need to take into account the globality of modern surveillance and give global surveillance a face and a name. Inspired by Derek Gregory's conceptualization of 'everywhere war', the here introduced notion of 'everywhere surveillance' provides a theoretical concept suitable for the study of global surveillance regimes. The concept allows for the analysis of complex surveillance apparatuses in all their intricacies, ruptures and interconnections and it allows for the study of the socio-technological and geographical characteristics and implications of global surveillance. 'Everywhere surveillance', the drawing together of heterogeneous, interoperable surveillance artefacts allows for surveillance to be carried out potentially everywhere and against everyone. This in turn is made possible by the capability of surveillance technologies to integrate global communication infrastructures. In the broader environment of techno-securitization the key characteristics of 'everywhere surveillance' lie in its globality, the production of heterogeneous geographies of surveillance, the blurring of lines between combatants and civilians as well as an alarming decline in transparency and accountability.